Studying possibility of using fruit powders in technology of sponge-cake semi-finished products - Доценко, Виктор Федорович; Мирошник, Юлия Анатольевна; Шидловская, Елена Брониславовна; Медвидь, Ирина Николаевна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper shows the possibility of enriching flour confectionery with powders of viburnum, ashberry and sea buckthorn for producing sponge-cake semi-finished products, as fresh fruit production is a seasonal product and does not provide a regular supply of biologically active substances into the population food ration. The influence of viburnum, ashberry and buckthorn powders on the amount and quality of gluten in dough was studied. In addition, the appropriateness of using SAS (surface-active substances) was substantiated. The data of amilograph studies for estimating the influence of fruit powders on the progress of gelatinization of flour raw materials is given. The structural and mechanical properties of dough during mixing, as well as changes of these properties during its fermentation was assessed by farinograph. Estimation of the influence of viburnum, ashberry and sea buckthorn powders on physical properties required carrying out studies by the Chopin alveograph. The conducted studies allow predicting improvements of such technological parameters as the sponge dough resistance, which plays an important role while mixing and baking, the baking loss reduction, and the increase of sponge-cake semi-finished products yield as well as prolongation of their shelf life, respectively. The research results can be used by production engineers in the confectionery industry along with restaurant businesses for developing new flour confectionery formulations.